Using Community-Based Social Marketing to Improve Energy Equity Programs - Marianne Schmink; Emily Ott; Paul Monaghan; Lee Hayes Byron; Alane Humrich; Jennison Kipp; Wendell Porter; Matthew Williams; Kimberly Davis; Fiona Hogan (EDIS)
This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication is part of a series that will help Extension agents, nonprofits, agency personnel and all types of community development practitioners to better understand the issue of high utility bills among low-income residents, the “energy equity gap” and what they can do to help. This document provides a description of how the CWC used Community-Based Social Marketing (CBSM) research to increase the impact of their program through a form of “action research” to guide practical changes. Their experience can provide useful lessons for Extension agents and all types of community development practitioners who are seeking to improve the impacts of their programs. https://edis.ifas.ufl.edu/wc407